The Imperial World-System and Cultures of Dissent in Thomas Hardy's Fiction - Jackson, Rena. author. aut Link
XVIII, 222 p. 2 illus.
Keywords: “Innovative and exciting, Rena Jackson’s book offers a wide-ranging and highly detailed exploration of the global dimensions of the imperialist world-system in Hardy’s work. It excavates the pulse of worker radicalism, anti-capitalist sentiment, and anti-imperial solidarity that beats beneath Hardy’s fiction, and makes a significant intervention into the fields of Victorian studies, postcolonial literature, and world literature.” —Michael Niblett, Associate Professor in Modern World Literature, University of Warwick and author of World Literature and Ecology (2020) "This revelatory book brings a whole new dimension to Thomas Hardy’s writing, and to Victorian Studies more broadly. Rena Jackson draws widely and convincingly on evidence which shows how both imperial and anti-colonial ideas were formative of Thomas Hardy’s works. I was wholly engrossed." —Corinne Fowler, Professor of Heritage and Colonialism, University of Leicester, author of Our Island Stories: Country Walks Through Colonial Britain (2024) "An excellent book which reveals in new ways the extent of Thomas Hardy’s global connections, problematizing notions of a shared national imperial identity, and situating his work alongside other novelists and poets." —Angelique Richardson, Professor of English, University of Exeter This is the first book-length study of imperial crossings in Thomas Hardy’s novels and short stories. Combining the strengths of world-literary and world-systems analyses with a cultural materialist approach, the study offers unparalleled coverage of global links in Hardy’s fiction, engaging, in addition, with a range of dissenting responses – at both formal and thematic registers – to the British world-system’s exploitative structures. Hardy’s prose outputs reveal that the empire, contrary to popular critical assumptions in postcolonial studies, did not harmonise the classes, genders or regions into a shared national imperial identity, culture or destiny. A major component of the study additionally includes comparative readings of the 'modern' world-system and imperial sociality in writings by Joseph Conrad, H. Rider Haggard, Elizabeth Gaskell, Rudyard Kipling, David Livingstone, and in Chartist poetry. The book will be an invaluable resource to teachers, students and enthusiasts working in the field of world literature, and in Victorian, postcolonial and settler colonial studies. Rena Jackson has published primarily in Hardy studies and postcolonial studies. She has taught and trained students at all degree levels at the University of Salford and the University of Manchester, and has introduced sessions on Hardy, imperial migrations and questions of class to sixth formers and on core and optional university modules. She completed her doctoral studies at the University of Manchester.